2020
DOI: 10.3390/jcm9072112
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of 18F-FDG-PET/CT in Patients with FUO

Abstract: Conventional diagnostic imaging is often ineffective in revealing the underlying cause in a considerable proportion of patients with fever of unknown origin (FUO). The aim of this study was to assess the diagnostic value of fluorine-18 fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG-PET/CT) in patients with FUO. We retrospectively reviewed 18F-FDG-PET/CT scans performed on 50 consecutive adult patients referred to our department for further investigation of classic FUO. Fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
(141 reference statements)
0
10
0
Order By: Relevance
“…This variation can be explained, in part, by differences in the definitions of FUO, diagnostic algorithms and the place of 18FDG-PET/CT within the algorithms, technique and model of the 18FDG-PET/CT scanners, and by how usefulness of the 18FDG-PET/CT is defined [ 29 ]. Moreover, studies differed in whether they included immunocompromised patients and the extent to which immunosuppressive medications were used, widening the discrepancies [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This variation can be explained, in part, by differences in the definitions of FUO, diagnostic algorithms and the place of 18FDG-PET/CT within the algorithms, technique and model of the 18FDG-PET/CT scanners, and by how usefulness of the 18FDG-PET/CT is defined [ 29 ]. Moreover, studies differed in whether they included immunocompromised patients and the extent to which immunosuppressive medications were used, widening the discrepancies [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The breakdown of how the test was classified by the judging clinicians and the statistical analysis of test properties were numerically comparable in those who underwent prior CT relative to the entire study cohort. Likewise, in a large study evaluating 18FDG-PET/CT in cases of FUO in which more than 70% of study participants had undergone prior chest and abdominal CT imaging, no correlation was detected between prior advanced diagnostic testing and whether 18FDG-PET/CT was found to be contributory [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous retrospective study of 112 patients with the same characteristics, demonstrated a sensitivity and specificity of 72.2% and 57.5% respectively [5]. In another recent retrospective study of 50 patients with classical FUO, sensitivity reported for PET-CT was higher 94.7%, and specificity was much lower 50% [23].…”
Section: Discussionmentioning
confidence: 93%
“…The increased availability of the technology over the past two and a half decades of its clinical implementation has also broadened its clinical applications, and imaging of inflammatory disease, e.g. in large vessel vasculitis, autoimmune encephalitis or fever without origin, are now established indications for FDG-PET/CT (29,(31)(32)(33). More recently, hybrid molecular imaging using FDG-PET/MRI has attracted attention for combining the superb imaging characteristics of both, MRI and PET in a simultaneous exam, defining a new imaging gold standard (34) with increasing sensitivity and specificity in soft tissue pathologies.…”
Section: Rationale For and Potential Of Systematic Clinical Studies On Targeted Molecular Imaging Using Positron Emission Tomography In Cmentioning
confidence: 99%